Supplementation of in vitro maturation medium with serum from dairy cows at early and late lactation in the in vitro production of bovine embryos - Collares, Letícia Franco; Pradieé, Jorgea; Borges, Morgana Alves; Mion, Bruna; Gindri, Patrícia; Fadrique, Janaína; Rincón, Joao Alveiro Alvarado; Pegoraro, Lígia Margareth Cantarelli; Schneider, Augusto; Corrêa, Marcio Nunes (Medicina Veterinária, 2019)
The transition period of dairy cows is characterized by several metabolic alterations, due to the negative energy balance, which negatively affects fertility. The aim of this study was to evaluate the effect of supplementing the in vitro maturation medium with serum from dairy cows at early and late lactation in the oocyte maturation on the rates of nuclear maturation, cleavage and initial embryo development. The cumulus-oocyte complexes (COCs) were randomly divided into treatments: LL: serum from four cows at 354 ± 3.8 days in milk (DIM); and EL: serum from four cows at 10.8 ± 4.8 DIM. Subsequently, the COCs were submitted to maturation, fertilization; and in vitro culture in an incubator at 39°C with 5% CO2. For analysis of nuclear maturation; oocytes were collected after IVM, denuded and stained with Hoechst®. No difference was observed in the number of oocytes that reached metaphase II among treatments. The cleavage rate was not different between LL (59.3%; 320/540) and EL (47.0%; 243/517) treatments (P>0.05), as embryonic development between LL (15.0%; 81/540) and EL (16.6%; 86/517) (P>0.05). It was concluded that supplementation with serum from cows at different lactation periods during the bovine oocyte IVM did not influence the results of in vitro embryo production.